Study on Representation of Dalit in Mulk Raj Anand’s Untouchable and Omprakash Valmiki: Exploring Dalit Memoirs: Representation and Resistance (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Dalit Memoirs is a collection of essays written in the style of reminiscing about the essayist's past. As it is, it aids the Dalit readers in igniting their desire for change. Dalit authors believe that the most important character in their self-portraiture is the validity of experience. The basis for Dalit literature in Hindi was created by Valmiki's self-portrait. Joothan has been a pioneering Hindi life report with a personal - critical standpoint among the Dalits. Joothan A Dalit's Life is claimed to have a voice with a diverse range of topics. The substance adds to Dalit history, and its depiction serves as a solace to oppressors. The first line of the poem critiques the location as well as the members of Valmiki's caste. The majority rule system in India has created an opportunity for Dalits to discuss their experiences. Despite what one would think, he shows the harsh reality vividly and underscores that India has failed to fully fulfil its obligations under the Indian constitution of independence. Joothan sarcastically criticises the constitution for its promissory note, raising Dalit voices demanding a place in the current society for their relatives. Mulk Raj Anand believes that a writer should be the fiery voice of the people and be able to present a fresh view of life, comprehending the hurts, frustrations, and goals of others, while speaking about the actual test of novelists the other caste sympathiser. It would be honing his nascent skills of expression, which transforms all emotions, ideas, and experiences into art. The topic of untouchables seems to have gone unaddressed in his book Untouchable. Undoubtedly, Raj Anand has expressed worry over the mistreatment of an oppressed class in Untouchable Mulk. He is, without a doubt, the untouchable caste's fiery voice. However, if the writer's purpose is to turn words into prophesy, as Anand claims, the reader in Untouchable seems to overlook this question via the dramatisation of Bakha.